Alcohol use disorder and associated factors among individuals living with HIV in Hawassa City, Ethiopia: a facility based cross- sectional study - Bereket Duko; Alemayehu Toma; Yacob Abraham (BMC, 2019)
Abstract Background Individuals living with HIV/AIDS with co-occurring harmful alcohol use may require specialized intervention or even multi-disciplinary team follow-up and management. This study was aimed to assess alcohol use disorder and associated factors among people living with HIV/AIDS in Hawassa city, Ethiopia, 2019. Methods A facility based cross-sectional study was conducted among 195 people living with HIV/AIDS who had follow-up visit at Hawassa University Comprehensive Specialized hospital. A systematic sampling technique was used to recruit the study participants. Alcohol used disorders identification test (AUDIT) was used to measure alcohol consumption, drinking behaviors, and alcohol-related problems. The binary logistic regression model was used to see the association between alcohol use disorder (AUD) and the independent variables. The strength of association was measured by odds ratios with 95% confidence intervals. Statistical significance declared at P < 0.05. Results The mean age of the study participants was 29.88 (±SD = 10.89) years. The magnitude of alcohol use disorder among people living with HIV/AIDS was 31.8%. Being male [AOR = 2.43, (95% CI: 1.76, 5.76)], having poor social support [AOR = 1.34, (95% CI: 1.12, 6.73)], being medication non-adherent [AOR = 1.78, (95% CI: 1.33, 6.79)], current khat chewing [AOR = 1.67, (95% CI: 1.16, 5.45)] and current cigarette smoking [AOR = 3.76, (95% CI: 2.16, 7.54)] had statistically significant association with alcohol use disorder. Conclusion In the current study, magnitude of alcohol use disorder among people living with HIV was high and, calls for integrating services provided to HIV patients in HIV care and treatment clinic which enhances timely detection and management of AUD cases. This also alerts the stakeholders in HIV prevention and control programs to invest a greater efforts to retain patients in addiction treatment and rehabilitation centers. Lastly, appropriate screening and health education on consequences of alcohol use disorder is warranted.